PEMBINAAN DAN PELATIHAN PENULISAN PAPAN NAMA DWIAKSARA SESUAI PASANG AKSARA DI KECAMATAN BANJARANGKAN KABUPATEN KLUNGKUNG - Sulibra, I.K.N.; Suryati, N.M.; Erawati, N.K.R.; Puspawati, L.P.; Suardiana, I.W. (Buletin Udayana Mengabdi, 2018)
The existence of language (including Bali with language anggah-ungguh or sor singgih as well as the script system) has important roles and functions in Balinese culture preservation. Bali with its letter is being underestimated and even marginalized so that did not get serious attention from the government. It can be seen that nowadays Balinese does not be an independent subject of lesson however it classified into vocational education and arts. This is certainly a major impact for the survival of the language with its script system. It could be compared in developed countries such as Japan, China, Korea; the letters are as elevated as displayed in shops, public places and the other places that do not use the Latin alphabet. This term also imitated by the neighboring countries such as Vietnam, Thailand, and Myanmar. Actually the government of Bali before the 2000 had give enough attention to the existence of language, literacy, and Balinese literary by made a local regulations of the use of the Balinese on billboards name, a sacred place, office name, and others. The manners in Balinese letters writing in traditional and modern, bilingual and multilingual terms are arranged in that regulation. However, in practice that is not as expected. It can be seen and observed by the used of Balinese in nameplate is lack even almost nothing. Although there are some sides use it, however mostly they are wrong in the writing. Certainly, it is bad for the survival of Balinese script.